Memory, Family, and Community in Roman Ephesos - Kalinowski, Angela (Cambridge University Press, 2021)
Cover -- Half-title -- Title page -- Copyright information -- Dedication -- Contents -- List of Figures -- List of Maps -- List of Tables -- Acknowledgments -- List of Abbreviations -- Introduction: Memory, Family, and Community in Roman Ephesos -- Context -- Structure of This Study -- 1 Community, Identity, and Memory in Roman Ephesos -- Ephesos as a milieu de mémoire: Memory is Inscribed on the City -- Euergetism and Its Monuments -- Ephesian and Roman Identities -- Communities and Inscriptions -- Inscribing Communities -- Monuments, Materiality, and Memory -- Collective Memory and Rituals That Keep in Mind -- Conclusions -- 2 The Vedii: A Family's History in Ephesos -- The Earliest Vedii: Italian Origins, Italian Cultural Affiliation -- The Vedii of Ephesos: Family Strategies -- The Union of the Vedii Antonini and the Claudii -- The Union of the Vedii and the Flavii, Twice -- The Flavii Vedii: Descendants of Vedia Phaedrina and T. Flavius Damianus -- What's in a Name? A Genealogical Inscription, Onomastics, and Memory -- Conclusions -- 3 ''Great is Artemis of the Ephesians!'' The Vedii and the Goddess of Ephesos -- Ephesos, Artemis, and Her Festivals -- A Priestess of Artemis: Vedia Marcia -- The Prytaneion, prytaneis, and kourêtes in Ephesos -- The Vedii and the Cults of the Prytaneion -- Gifts to Artemis: The So-called Stoa of Damianus -- Gifts to Artemis: A Dining Hall in Her temenos -- Gifts to Artemis: An Inheritance -- Commemorating Generosity: A Family Statue Group (In Fact, Two) -- Conclusions -- 4 Fun and Games in Roman Ephesos: The Vedii, the Agonistic Festivals, and the Imperial Cult -- The Great Epheseia -- The Olympia of Ephesos -- The Hadrianeia [Commodeia] -- The Great Asklepieia -- The Vedii as Priests and Priestesses of the Imperial Cult -- The philovedioi philoploi: The Vedii as Owners of a ludus in Ephesos -- Conclusions.